The title of the article in English: Measles in the Republic of Guinea in 2019-2020: epidemic features and population immunity - Irina Nikolaevna Lavrentieva (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Introduction. In connection with the Ebola epidemic in West African States, including the Republic of Guinea, there was a violation of the measles immunization program. The share of seronegatives to the measles virus in 2017 was 52.4% of the number of examined individuals. In 2018, a high proportion of measles cases among children aged 1-5 years (61.6%) was identified. In order to stop the outbreak in 2018, the Supplemental Immunization Campaign was conducted in the Konakri and Nzerecare prefectures in the Republic of Guinea. The aim of this study was to study the epidemic situation of measles and to assess the population immunity to the measles virus in the Republic of Guinea in 2019-2020. Materials and methods. For the presence of specific antibodies, 1697 blood serum samples from residents of different regions of the Guinea, aged from 7 months to 76 years, obtained in 2019-2020, were retrospectively tested. The ELISA test systems "Anti - Measles Virus ELISA (IgM) Euroimmun" and "Anti-Measles Virus ELISA (IgG) Euroimmun" (Germany) were used. The presence of IgM antibodies to the measles virus in the blood serum was assessed as an acute measles infection. Statistical analysis was performed using the software package Statistica v. 6.0. Results. Blood sera (n=638) were tested for the presence of IgM-measles, in 46.6% of cases the diagnosis was confirmed by laboratory tests. The largest share of the total number of cases (61.6%) – children 1-4 years. The second most important age group is 5-9 years, the third is children under 1 year: 18.5%, and 11.8 % of the total number of patients, respectively. Measles was registered in vaccinated patients: in 7.4% of the total number of laboratory-confirmed cases. 1059 people were examined for IgG - measles. The lowest seroprevalence rate was found among children under 4 years of age, 47.8%. The highest (85.5%) was  found among people 40 years and older. Conclusion. Measles in GR remains a poorly controlled infection. As in the previous years of observation (2017-2018), children under 5 years of age are the most vulnerable cohort of the population, despite the DI campaign conducted in 2018 in a number of territories of the country. More problems in the control of measles infection in the the Republic of Guinea are expected in the period from 2021, as along with the COVID-19 epidemic, Ebola is again registered in the country. The Republic of Guinea is particularly in need of assistance from the international community to implement the WHO measles elimination program on a global scale.